PELATIHAN DAN DEMPLOT DIVERSIFIKASI OLAHAN IKAN GABUS BAGI KELOMPOK PETANI AIR TAWAR DI JURANG MANGU: PENINGKATAN KETERAMPILAN DAN NILAI TAMBAH PRODUK - Tri Ika Jaya Kusumawati; Windhy Widhyanty; Ravindra Safitra Hidayat (Universitas Mataram, 2026)
Channa striata (snakehead fish) is a freshwater commodity with high nutritional value and strong economic potential. However, fish farmers in Jurang Mangu still sell their harvests in fresh form, facing fluctuating prices and unutilized unsold or less-fresh fish. The abundant harvests have not yet been processed into value-added products, resulting in suboptimal economic potential and low business competitiveness. This community service program aims to enhance fish farmers’ skills in diversifying snakehead fish products through training on the use of simple fish processing equipment. The program involved 20 participants and was conducted through hands-on training, observation, and pre–post skill assessments using a simple rubric. Prior to training, 75% of participants were unable to process snakehead fish; after the program, 100% successfully produced at least one processed product, and 60% managed to create two or more types. An economic analysis showed that processed fish products could be sold at Rp120,000–150,000/kg, higher than fresh fish (Rp90,000/kg), which often led to a Rp50,000/kg loss for small or dead fish. Additional margin analysis indicated a selling price of Rp45,000/kg and variable costs of Rp30,000/kg, yielding a profit margin of Rp15,000 or 33.33% per kilogram.The diversification training effectively improved fish farmers’ processing skills in a measurable way and generated significant value-added opportunities. The results demonstrate a notable increase in participants’ capabilities and potential profitability, contributing to greater welfare and competitiveness for freshwater fish farming groups in Jurang Mangu.